2008
DOI: 10.1007/s11252-008-0051-1
|View full text |Cite
|
Sign up to set email alerts
|

The energy and mass balance of Los Angeles County

Abstract: We conducted an urban "metabolic" study of inputs and outputs of food, water, energy, and pollutants from Los Angeles County, USA. This region has been the subject of recent debate about the nature of population density and distribution as it relates to urban form and associated environmental impacts. We found that with the exception of food imports and wastewater outputs, inputs of resources and outputs of pollutants generally declined on a per capita basis from 1990 to 2000. Reductions likely reflected a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…However, this is not the case, as important pathways of water loss tend to be poorly monitored or unmonitored. For example, Ngo and Pataki (2008) found that less than 40% of imported water in Los Angeles County could be accounted for in measured wastewater discharge and runoff. In the western United States, much of the imported water used outdoors is presumably lost through ET, although this is highly uncertain as ET is arguably the most difficult component of the water budget to estimate in cities.…”
Section: Uncertainties and Future Directions In Urban Water Researchmentioning
confidence: 99%
“…However, this is not the case, as important pathways of water loss tend to be poorly monitored or unmonitored. For example, Ngo and Pataki (2008) found that less than 40% of imported water in Los Angeles County could be accounted for in measured wastewater discharge and runoff. In the western United States, much of the imported water used outdoors is presumably lost through ET, although this is highly uncertain as ET is arguably the most difficult component of the water budget to estimate in cities.…”
Section: Uncertainties and Future Directions In Urban Water Researchmentioning
confidence: 99%
“…Ngo and Pataki [18], and McGraw et al [19], accounted for GHG emissions for Los Angeles (CA, USA) and Chicago (IL, USA), respectively. Both accounted for a comprehensive set of in-boundary emissions; the former included transboundary emissions from food production and wastewater treatment, whereas the latter did not cover these categories, but did account for freight.…”
Section: Scopementioning
confidence: 99%
“…For example, a few studies have quantified fossil fuel CO 2 emissions at the scale of an entire county or city [16,17,[19][20][21]. Other studies have attempted somewhat smaller spatial scales by quantifying emissions at the census tract or 'community' level [22,23].…”
Section: Yuyu Zhou 1 and Kevin Gurney †2mentioning
confidence: 99%